Geology, petrology and geochemistry of the dome complex of Huequi volcano, southern Chile - Watt, S; Pyle, D; Mather, T (2011)
Huequi, a little-known volcano in the southern part of the Andean southern volcanic zone (SSVZ), shows a regionally unusual eruption style, mineralogy and geochemistry. The volcano comprises multiple highly-eroded lava domes. Past eruptions were accompanied by relatively minor explosive activity, most recently from 1890-1920. The rocks erupted by Huequi range from basaltic andesite to dacite, and are highly distinctive when compared to other volcanoes of the SSVZ, being K-poor and Al-rich, and containing euhedral hornblende phenocrysts. Overall compositions suggest a notably water-rich magma source, evolving through high levels of fractionation and subsequent degassing to produce highly porphyritic dome-forming andesites. The ultimate causes of water-rich magmas at this point in the arc remain unclear.